The role of EBV-encoded miRNA in EBV-associated gastric cancer - Liu, Ting; Zhou, Xiaoying; Zhang, Zhe; Qin, Yutao; Wang, Rensheng; Qin, Yanning; Huang, Yuqi; Mo, Yingxi; Huang, Tingting (Frontiers in Oncology, 2023)
Epstein-Barr virus (human herpesvirus 4, EBV) is a linear double-stranded DNA virus that infects over 90% of the population worldwide. However, our understanding of EBV’s contribution to tumorigenesis of EBV-associated GC (EBVaGC) remains incomplete. Recent advancements in EBVaGC research have highlighted that EBV-encoded microRNAs (miRNAs) play prominent roles in critical cellular processes such as migration, cell cycle, apoptosis, cell proliferation, immune response, and autophagy. Notably, the largest group of EBV-encoded miRNAs, known as BamHI-A rightward transcripts (BARTs), exhibit bidirectional effects in EBVaGC. For instance, they present both anti-apoptotic and pro-apoptotic functions and enhance chemosensitivity while also conferring resistance to 5-fluorouracil. Despite these findings, the comprehensive mechanisms through which miRNAs contribute to EBVaGC are yet to be fully elucidated. In this work, we summarize the current evidence of the roles of miRNA in EBVaGC, particularly with the application of multi-omic techniques. Additionally, we discuss the application of miRNA in EBVaGC in retrospective analyses and provide novel perspectives on the use of miRNA in EBVaGC in translational medicine.